Giacomo Puccini's Operatic Legacy and Its Study in the Practice of Vocalists - Semkin, Dmitry; Bushueva, Lyubov (Տիգրան Մեծ)
The purpose of this article is to analyze the Opera legacy of Giacomo Puccini from the standpoint of practical vocal pedagogy, which, according to the authors, is necessary for the formation of vocal and performing skills of young singers of the academic direction. The authors suggest a historical overview of the main works of the composer in this genre, based on the study of their vocal characteristics, and the author reveals the features of his unique Arioso-recitative style. Various research methods (the aesthetic, vocaltechnical and methodological analyses in particular) reveal that the works by G. Puccini are of particular significancefor the development of vocalists‟ singing breath, musicality, imaginative thinking, mastering of the technique of cantilena, continuous legato (as the basis of bel canto), improving the timbral colours of the voice, its dynamic nuances, developing the right senses of agogics.The above is confirmed by the analysis of the peculiarities of performance technique and interpretation of one of the composer‟s most famous works for the tenor voice–Calaf‟s aria “Nessun dorma” from the opera “Turandot” (which was the main subject of this study).
Keywords: Opera legacy